Access to Finance for Micro, Small, and Medium-Sized Enterprises in Bosnia and Herzegovina with a Focus on Gender : A Survey Report - World Bank Group (World Bank, Washington, DC, 2018)
This report provides a baseline analysis of the status of access to finance for micro, small, and medium-sized enterprises (MSMEs) with a particular focus on women entrepreneur' ability and constraints in accessing finance in order to develop and grow their businesses. It is based on a nationally representative survey of 542 enterprises conducted in Bosnia and Herzegovina (BiH) between September 2016 and February 2017. The survey is a continuation of the ongoing work on access to finance and builds upon an earlier supply-side study conducted by the World Bank during the 2014 IMF/World Bank Financial Sector Assessment Program (FSAP) Update, as well as on lessons learned from the BiH Enhancing SME Access to Finance Project. The objective of the survey is to further analyze the demand side constraints to private sector growth and enterprise performance related to or arising from lack of access to finance. The survey has the specific aim to determine the level of women entrepreneurs' ability and constraints in accessing finance in order to develop and grow their businesses.